Examining sources of variability in repeaters' L2 writing scores: The case of the PTE Academic writing section. (January 2019) - Barkaoui, Khaled
This study aimed to examine the sources of variability in the second-language (L2) writing scores of test-takers who repeated an English language proficiency test, the Pearson Test of English (PTE) Academic, multiple times. Examining repeaters' test scores can provide important information concerning factors contributing to changes in test scores across test occasions. Data consisted of the scores and background data (e.g., gender, age) and other covariates (e.g., context, interval between tests, number of tests attempted) for a sample of 1, 000 test-takers who each took PTE Academic three times or more. Multilevel modeling was used to estimate the contribution of various factors to variability in repeaters' PTE Academic writing scores across test-takers and test occasions. The findings indicated that changes in PTE Academic writing scores followed a quadratic trajectory (i.e., initial score increases followed by a decline) and that, as expected, test-taker initial overall English language proficiency (as measured on other sections of the test) was the strongest predictor of differences in PTE Academic writing scores at test occasion one as well as variance (across test-takers) in the rate of change in writing scores over time. Measures of retesting effects were not significantly associated with changes in writing scores, while test-taker factors (e.g., age, gender, and purpose for taking the test) were significantly associated with writing scores at test occasion one, but not with the rate of change in writing scores over time. The study highlights the value of examining repeater' L2 test scores and concludes with a call for more research on the sensitivity of L2 proficiency tests to changes in L2 proficiency over time and in relation to L2 instruction.